The multi-situatedness of biographical narratives: Contributions to critical migration research - Mercy Mashingaidze; Eva Shamiran Youkhana (University of Bonn, Center for Development Research (ZEF), 2022)
One's own life story is made up of thousands of events that influence person's choices from birth to death. These events are to be understood as references that accompany a person's positioning in society and are condensed in individual relationships. Biographies are an attempt to relate the social position to the individual positioning that forms the positionality of everyone in his socio-material world. They allow to disentangle the interplay of our roots and routes so often referred to in individual migration histories. This working paper presents two selected narrative interviews conducted within the framework of different research projects on migration with a translocational lens. Taken out of the different contexts, namely a Zimbabwean migrant in London and a Colombian migrant in Madrid, we show the benefits of an interview technique that allows conclusions to be drawn from the subjective perspective on social structures that shape individual lives. By zooming into the life stories, influential factors that are significant but often overlooked in transnational migration research become visible. Beyond social relations, these embrace the material world, the spatial and urban surroundings, cultural references and technologies as much as the embodied individual experiences.
Keywords: 330; Biographic interview; translocational positionalities; critical migration research